PENDUGAAN KANDUNGAN MERKURI DAN SIANIDA DI DAERAH ALIRAN SUNGAI (DAS) BUYAT MINAHASA - Bobby J. Polii & Desmi N. Sonya (EKOTON, 2012)
Since 1900, gold mining activity has been conducted in northern Sulawesi. The activity can be grouped into (1) small-scale, and (2) large-scale activities. Both activities may increase income for local government, opportunity for labor and investment, which give positive impact to other economic activities. However, the mining activity may give negative impact to environment, such as landscape changes, destruction of watershed, potentially as a source of pollutants and other dangerous and toxic substances. Mercury (Hg) and cyanide (CN) are two of pollutants generate from mining activity. Uncontrolled uses of both (mercury and cyanide) pollutants may pollute the environment and the pollutants may accumulate into marine organism food chance.